He is a glutton and a drunkard : deviant consumption in the Hebrew Bible - Welton, Rebekah, (Biblical Interpretation Series;, 2020)
"In 'He is a Glutton and a Drunkard': Deviant Consumption in the Hebrew Bible Rebekah Welton uses interdisciplinary approaches to explore the social and ritual roles of food and alcohol in Late Bronze Age to Persian-period Syro-Palestine (1550 BCE-400 BCE). This contextual backdrop throws into relief episodes of consumption deemed to be excessive or deviant by biblical writers. Welton emphasises the social networks of the household in which food was entangled, arguing that household animals and ritual foodstuffs were social agents, challenging traditional understandings of sacrifice. For the first time, the accusation of being a 'glutton and a drunkard' (Deut 21:18-21) is convincingly re-interpreted in its alimentary and socio-ritual contexts".